2017
DOI: 10.1061/(asce)me.1943-5479.0000555
|View full text |Cite
|
Sign up to set email alerts
|

Corrupt Practices in the Construction Industry: Survey of Ghanaian Experience

Abstract: Globally, corruption presents a major risk that reduces construction project performance by inflating costs and reducing the quality of infrastructure commissioned. In developing countries, corruption 8 stifles economic development and engenders social inequality. This paper uncovers the prevalence and 9 forms of corrupt practices within the developing country of Ghana using a structured questionnaire survey to elicit direct knowledge and lived experiences of construction practitioners. Research findings illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(123 citation statements)
references
References 37 publications
5
118
0
Order By: Relevance
“…Of the three biggest economies in Africa, namely, Nigeria, Egypt and South Africa, Nigeria is the most corrupt. Nigeria is also more corrupt than neighbouring Ghana where Ameyaw et al (2017) and Bowen et al (2007a), respectively, found evidences of widespread corruption (see Figures 1 and 2). Whereas corruption in the country is not confined to any particular industry, studies have shown Nigeria has recently renewed efforts towards stamping out corruption in every area of its national life.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Of the three biggest economies in Africa, namely, Nigeria, Egypt and South Africa, Nigeria is the most corrupt. Nigeria is also more corrupt than neighbouring Ghana where Ameyaw et al (2017) and Bowen et al (2007a), respectively, found evidences of widespread corruption (see Figures 1 and 2). Whereas corruption in the country is not confined to any particular industry, studies have shown Nigeria has recently renewed efforts towards stamping out corruption in every area of its national life.…”
Section: Introductionmentioning
confidence: 95%
“…Most previous studies identified unethical practices in the construction industry, without being solely specific to the tendering stage of procurement (Adnan et al 2012;Ameyaw et al 2017;Le et al 2014;Shan et al 2016;Vee & Skitmore 2003). Ray et al (1999), who focused solely on the tendering stage of procurement, concentrated on ascertaining the extent to which the principles enshrined in the Interim Australian Standard Code of Tendering were accepted and applied in the Australian construction industry.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The sample size was relatively small, yet it is deemed adequate, compared with other empirical corruption-related studies in construction management. As evidence, Vee and Skitmore (2003), Ameyaw et al (2017) and Brown and Loosemore (2015) conducted studies with sample sizes of 31, 35 and 23, respectively.…”
Section: Samplingmentioning
confidence: 92%
“…The identified procurement irregularities -the 18-list indicators -were captured in a questionnaire survey. The use of questionnaires as the main data instrument for this study was justified, given that this method offers a valid and reliable source of information quickly, with minimal resources required (Ameyaw et al, 2017). The survey was used, as this method warrants anonymity, and maintains the anonymity of potential respondents, being of outmost importance in conducting research on a sensitive topicrelated to corruption (Hoxley, 2008;Ameyaw et al, 2017).…”
Section: Surveymentioning
confidence: 99%
See 1 more Smart Citation